Caracterização morfológica e histoquímica de fígados bovinos com fasciolose crônica - Paula, Fabiana Maria do Amaral Bravo de (2014)
Bovine fascioliasis produces severe damage to the liver and is caused by the parasite Fasciola hepatica. This study aimed to characterize the morphological and histochemical changes of the liver tissue with chronic fascioliasis in cattle, as well as identify the foci of metaplasia. Were collected 47 bovine livers condemned for fascioliasis and 12 normal livers used to control in the slaughterhouse from Atilio Vivacqua, ES. Counting parasites and collecting five fragments of each lobe, right and left livers affected by illness, totaling 235 samples per lobe was taken. The control group were collected only a fragment of liver. All material was fixed in 10% formalin and subjected to histological analysis and stained by HE and PAS. Microscopic analysis were based on the distribution of fibrosis in degrees 1, 2 and 3 and in the type and intensity of the inflammatory infiltrate, followed by evaluation of the foci of metaplasia. Statistical evaluation was taken by descriptive method and by Mann-Whitney test at 5% probability. No difference was observed between the number of parasites per lobe but the left lobe showed higher parasitic intensity. Fibrosis was observed in all samples and prevailed grade 1. There was significant difference between degree of fibrosis in the liver with fascioliasis and normal liver and between the hepatic lobes. The inflammatory infiltrate showed a predominance of mononuclear cells of discrete intensity. Was difference between the intensity of the inflammatory infiltrate between the right and left lobes of the liver. The presence of eosinophils was also observed, but at a lower amount. In relation to metaplasia foci was observed that 53.19% of the samples of the right lobe showed these changes while in the left lobe, this percentage was 57.45%, however, no significant differences were found between the occurrence of metaplasia between the right and left lobes. Was observed higher prevalence of mucus production in discrete to moderate intensity, however, there was no difference between the amount of mucus produced between the hepatic lobes. We conclude that fibrosis is most outstanding change in livers chronically infected with F. hepatica and was more evident in the left hepatic lobe. The inflammatory infiltrate was predominantly mononuclear and discrete and also more prevalent in the left lobe. The foci of metaplasia are present in livers with chronic fascioliasis and have differences in the intensity of mucus produced.